The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3389/fnins.2020.00582
|View full text |Cite|
|
Sign up to set email alerts
|

EEG Biomarkers Related With the Functional State of Stroke Patients

Abstract: Introduction: Recent studies explored promising new quantitative methods to analyze electroencephalography (EEG) signals. This paper analyzes the correlation of two EEG parameters, Brain Symmetry Index (BSI) and Laterality Coefficient (LC), with established functional scales for the stroke assessment. Methods: Thirty-two healthy subjects and thirty-six stroke patients with upper extremity hemiparesis were recruited for this study. The stroke patients where subdivided in three groups according to the stroke loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 47 publications
(63 reference statements)
0
56
0
1
Order By: Relevance
“…Fourth, while we used a broad range of scales, different scales and assessment methods could yield different results. Fifth, emerging qEEG approaches (Sebastián-Romagosa et al, 2020) or other analysis tools could also provide further insight.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, while we used a broad range of scales, different scales and assessment methods could yield different results. Fifth, emerging qEEG approaches (Sebastián-Romagosa et al, 2020) or other analysis tools could also provide further insight.…”
Section: Discussionmentioning
confidence: 99%
“…The sensorimotor oscillations that mainly comprise the rolandic alpha [(7–13) Hz] and beta [(14–30) Hz] rhythms have been thoroughly used to study cortical involvement during sensorimotor tasks ( Ramos-Murguialday and Birbaumer, 2015 ; López-Larraz et al, 2018 ), being quantified as the event-related (de)synchronization (ERD/ERS) ( Pfurtscheller and Lopes da Silva, 1999 ). Furthermore, it has also been used as a feature for neuromodulation of sensorimotor neural network via proprioception and haptics ( Ray et al, 2020 ; Sebastián-Romagosa et al, 2020 ). To date, only a few studies have reported how oscillatory activity measured with EEG is modulated by NMES ( Vidaurre et al, 2016 , 2019 ; Tu-Chan et al, 2017 ; Corbet et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Abnormalities such as a decrease in rapid frequencies are found when cerebral blood flow (CBF) is diminished during ischemia [13]. In stroke patients, EEG power is significantly impacted, with an increase in delta (1-4 Hz) power accompanied by decreases in alpha (8)(9)(10)(11)(12)(13)(14) and beta (14-30 Hz) power, resulting in a diffuse slow-wave EEG pattern. Recently, few studies have emphasized on the usability of EEG to support and understand brain changes at rehab centers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, few studies have emphasized on the usability of EEG to support and understand brain changes at rehab centers. ese tools can help identify changes in EEG biomarkers and parameters during therapy that might lead to improved therapy methods and functional prognoses [14]. us, we have made an attempt to have a real-time monitoring of few of the parameter with the use of an IoT-based system.…”
Section: Introductionmentioning
confidence: 99%